Pengaruh Disiplin Pegawai Dan Pengawasan Terhadap Kinerja Pegawai Pada Dinas Pemberdayaan Masyarakat Dan Desa Provinsi Maluku - Megawati Manik; Hendry Selanno; Julia Th Patty (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2022)
This research is a quantitative research type. Aims to determine the effect of employee discipline and supervision on employee performance at the Maluku Province Community and Village Empowerment Office against the background of problems regarding employee performance that have not been maximized. The sample in this study amounted to 41 respondents. The data collection techniques used were observation, questionnaires using multiple linear regression analysis models, and classical assumption tests. The results of this study indicated that the effect of employee discipline on employee performance partially provided an effective contribution of 75.3%. The effect of supervision on employee performance partially provided an effective contribution of 75.5%. Simultaneously, employee discipline and supervision made an effective contribution of 71% to employee performance, and 29% was influenced by other variables not examined by researchers. This is seen based on the value obtained from data processing using the SPSS version 26 application, which showed that the significance value (sig) of the T test and F test is smaller than the probability value of 0.05. In improving employee performance, of course, other variables are needed to encourage better employe performance.